2017
DOI: 10.1002/jso.24892
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy in retroperitoneal sarcoma management

Abstract: Surgery is potentially curative for primary non-metastatic retroperitoneal soft tissue sarcomas (RPS), although patients remain at risk for local recurrence. To reduce this risk, the addition of radiotherapy to radical surgery may be considered. Nevertheless, level I evidence to support radiotherapy is currently lacking. The results from the EORTC-STBSG 62092-22092 studying this question are awaited. This manuscript addresses issues to consider when radiation-oncologists engage in a multidisciplinary treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…National data showed that radical resections combined with radiotherapy were only adopted in a minority of stage I RPS patients. Due to a potential increase in overall mortality and long-term dysfunctions ( 18 ), determining the impact of radical resections and radiotherapy in combination is crucial ( 19 ). Given its potential toxicity and poor evidence, radiotherapy shows a narrow indication in RPS-related guidelines ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…National data showed that radical resections combined with radiotherapy were only adopted in a minority of stage I RPS patients. Due to a potential increase in overall mortality and long-term dysfunctions ( 18 ), determining the impact of radical resections and radiotherapy in combination is crucial ( 19 ). Given its potential toxicity and poor evidence, radiotherapy shows a narrow indication in RPS-related guidelines ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…An international collaborative phase III trial (EORTC 1809 STRASS II) assessing neoadjuvant chemotherapy in dedifferentiated liposarcoma and leiomyosarcoma will be of great interest, noting that these were the most common histologies in our cohort. Adjuvant radiotherapy following R0/R1 resection is not of proven benefit, and is associated with substantial toxicity 23,24 . Adjuvant chemotherapy after complete resection is not of proven benefit in RPS 25 ; there may be a role in selected cases following consideration within experience multidisciplinary units 15 .…”
Section: Discussionmentioning
confidence: 99%
“…3 Although preoperative radiotherapy has been shown to decrease the local recurrence in a few studies, their role is not definite so far. 6 Prognosis varies with the histological subtypes, tumour grade and completeness of the surgical resection. 3 Twitter Souradeep Dutta @souradeep Contributors The idea for the article by MT.…”
Section: Descriptionmentioning
confidence: 99%